Understanding the Immune-Stroma Microenvironment in B Cell Malignancies for Effective Immunotherapy - Apollonio, Benedetta; Ioannou, Nikolaos; Papazoglou, Despoina; Ramsay, Alan G. (Frontiers in Oncology, 2021)
Cancers, including lymphomas, develop in complex tissue environments where malignant cells actively promote the creation of a pro-tumoral niche that suppresses effective anti-tumor effector T cell responses. Research is revealing that the tumor microenvironment (TME) differs between different types of lymphoma, covering inflamed environments, as exemplified by Hodgkin lymphoma, to non-inflamed TMEs as seen in chronic lymphocytic leukemia (CLL) or diffuse-large B-cell lymphoma (DLBCL). In this review we consider how T cells and interferon-driven inflammatory signaling contribute to the regulation of anti-tumor immune responses, as well as sensitivity to anti-PD-1 immune checkpoint blockade immunotherapy. We discuss tumor intrinsic and extrinsic mechanisms critical to anti-tumor immune responses, as well as sensitivity to immunotherapies, before adding an additional layer of complexity within the TME: the immunoregulatory role of non-hematopoietic stromal cells that co-evolve with tumors. Studying the intricate interactions between the immune-stroma lymphoma TME should help to design next-generation immunotherapies and combination treatment strategies to overcome complex TME-driven immune suppression.